2020
DOI: 10.1016/j.electacta.2020.136688
|View full text |Cite
|
Sign up to set email alerts
|

Shifting-reference concentration cells to refine composition-dependent transport characterization of binary lithium-ion electrolytes

Abstract: We present a novel 'shifting-reference concentration-cell' method, altering the traditional protocol for measuring liquid-junction potentials by using a sequence of reference concentrations in regularly spaced intervals, rather than a fixed reference. The method, applied to solutions of lithium hexafluorophosphate (LiPF6) in propylene carbonate (PC) and ethyl methyl carbonate (EMC) at 25 °C, helps to determine thermodynamic factors more accurately, and is useful across a wider concentration range. For LiPF6:PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(127 citation statements)
references
References 38 publications
10
117
0
Order By: Relevance
“…Wang et al showed this by comparing a PC-based electrolyte with an EMC-based electrolyte. [11] G4 has a ε r that lies between PC and EMC (7.91 vs. 64.92 and 2.96 respectively), and its χ M dependence on concentration agrees with this. The concentration at which the curve crosses χ M = 1 is indicative of when ion-solvent effects out-compete ion-ion effects.…”
Section: Thermodynamic Factorsupporting
confidence: 65%
“…Wang et al showed this by comparing a PC-based electrolyte with an EMC-based electrolyte. [11] G4 has a ε r that lies between PC and EMC (7.91 vs. 64.92 and 2.96 respectively), and its χ M dependence on concentration agrees with this. The concentration at which the curve crosses χ M = 1 is indicative of when ion-solvent effects out-compete ion-ion effects.…”
Section: Thermodynamic Factorsupporting
confidence: 65%
“… 9 , 10 D a p p is characterised through Fick’s laws of diffusion, and is defined as the proportion of current carried by the cation. Each is conventionally measured through different electrochemical techniques, with D a p p occasionally assessed using restricted-diffusion cells, 7 , 11 , 12 and from either the Hittorf method 7 , 11 , 13 15 , pulsed-field gradient NMR 16 or a “steady-state current” method, like the Bruce–Vincent. 17 19 Each have their limitations, with Hittorf often requiring large volumes of electrolyte and not being able to measure in situ concentration changes, and steady-state methods making assumptions such as the electrolyte being infinitely dilute (perfectly ideal).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other lithium-ion electrolytes, D app was quite low, with 1M PC and EMC-based electrolytes exhibiting values 2-6 times higher. [7,11] Decreasing D app with concentration is a result of increasing association of ions and increasing complexation of Li + with G4; an increasing frictional , showing an increase at low concentrations, then generally plateauing, and increasing again at 2m. e) (dc/dx) x=0,L , which was quite constant at low concentrations but increased rapidly after 1m.…”
Section: Diffusion Coefficientmentioning
confidence: 99%
“…Illustrated in Figure 4f, the electrolyte behaved according to extended Debye-Huckel theory described in ESI †, section 3.5; χ M is plotted against the square-root of concentration. [35] Similar to Hou [7] and Wang's [11] approach, the data was fitted with an extended Debye-Huckel Guggenheim equation; a x 1/2 power series. [40] This shape is akin to those of other organic-based electrolytes; [7,11,13,14]at low concentrations, a drop in χ M suggests long-range ion-ion association dominates, but at higher concentrations it is shorter range solvation effects that dominate.…”
Section: Thermodynamic Factormentioning
confidence: 99%
See 1 more Smart Citation